(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Nowadays, surveillance has become a need in any private or public area due to the increase in the number of threats such as robberies, terrorists, and abusers. In this paper, an efficient wireless monitoring system using Radio Frequency Identity (RFID) is proposed. The aim of this system is to detect a specified target during his movement in the covered region. The efficiency of the proposed system is clearly noticed through both storage capacity and power consuming reduction. This is done by dominating the work of cameras operation when receiving a signal from the distributed detectors. The obtained results show the saving in power and storage capacity is more efficient in comparison with the traditional monitoring systems. This work has two implemented sides; hardware and simulated environment that using Microsoft visual studio (C# framework).